Kajian yuridis peraturan daerah mengenai larangan pengemis - Nyimas Aziziah Jehan Yusaviera; Holiyatul Farodis; Yarris Adhial Fajrin (University of Merdeka Malang, 2020)
The increasing number of people with social welfare problems has received serious attention from the government. The majority of people with social welfare problems are due to poverty. The mindset of beggars is also the mindset of the community, often when people see beggars they always feel sorry and pity. The government has taken many steps, one of which is the enforcement of laws and regulations regarding the prohibition of begging in public. This writing method is to use the normative method, namely research that focuses on the study of the application of a rule or norm in positive law. The reason for this is that the Regional Regulation (Perda) of Malang City Number 2 of 2012 concerning Public Order and the Environment still creates regulatory ineffectiveness. This step aims to overcome public begging which can disrupt public order. The statutory regulations issued by the Malang City Government to overcome these social problems are the Malang City Regional Regulation Number 2 of 2012 concerning Public Order and the Environment.How to cite item: Wijaya, N., Perwira, T., Rusman, R. (2020). Politik hukum dalam pembentukan undang-undang Republik Indonesia nomor 18 Tahun 2019 tentang pesantren. Jurnal Cakrawala Hukum, 11(2), 194-201. doi:https://doi.org/10.26905/idjch.v11i2.3867